Pengaruh Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO) Net Profit Margin (NPM) dan Earning Per Share (EPS) Terhadap Harga Saham Pada Sektor Industri Peralatan Rumah Tangga Periode 2013-2017 - Gustriana Rohanda (Science of Management and Students Research Journal (SMS), 2020)
The purpose of this research is to find out and analyze the influence of the effect of Current Ratio (CR), Debt To Asset Ratio (DAR), Total Asset Turn Over (TATO) NetProfit Margin (NPM) and Earning Per Share (EPS) on Stock Prices in the Sector Household Appliances Industry Period 2013-2017.The type of data used in this study is secondary data, namely data in the form of financial statements issued by non-managing organizations, whose data sources are obtained from the Indonesia Stock Exchange. Data analysis in this study using multiple linear regression and using SPSS ver. 20Based on the tests conducted partially, it is known that the variables that affect stock prices are Earning Per Share (EPS), which is the EPS tcount of 3.990 which will be compared with the ttable value of 2.776 tcount> ttable ie 3.324> 2.776 and EPS significance of 0.002 according to choice significance <0.05, it can be concluded that EPS opposes Stock Price, but on Curren Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), Net Profit Margin (NPM), partially meaningless and not significant.For further researchers need to choose a company in another field to obtain more valid results to test the effect of current ratio (CR), debt to asset ratio (DAR), total Asset turnover (TATO), net profit margin (NPM) and earnings per share (EPS ) jointly influences the Share Price. The company is expected to be able to maintain financial statements well, not increase the company's debt for capital and for investors or prospective investors who will invest in order to analyze the company's financial statements before investing.